2018
DOI: 10.1016/j.ibmb.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A deep insight into the male and female sialotranscriptome of adult Culex tarsalis mosquitoes

Abstract: Previously, a Sanger-based sialotranscriptome analysis of adult female Culex tarsalis was published based on ∼2000 ESTs. During the elapsed 7.5 years, pyrosequencing has been discontinued and Illumina sequences have increased considerable in size and decreased in price. We here report an Illumina-based sialotranscriptome that allowed finding the missing apyrase from the salivary transcriptome of C. tarsalis, to determine several full-length members of the 34-62 kDa family, when a single EST has been found prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…D7 proteins are among the most abundant components in the salivary glands of several blood-feeding arthropods and are distantly related to the arthropod odorant-binding protein superfamily [7][8][9][10] . The D7s belong to a multi-gene family that evolved through gene duplication events, resulting in long forms and truncated versions of a duplicated long form, known as short forms 8 .…”
mentioning
confidence: 99%
“…D7 proteins are among the most abundant components in the salivary glands of several blood-feeding arthropods and are distantly related to the arthropod odorant-binding protein superfamily [7][8][9][10] . The D7s belong to a multi-gene family that evolved through gene duplication events, resulting in long forms and truncated versions of a duplicated long form, known as short forms 8 .…”
mentioning
confidence: 99%
“…This phenomenon is not unique to RPW and has also been confirmed in many other insects, such as T. castaneum [3], T. molitor [8], Nicrophorus vespilloide [37], and Helicoverpa armigera [34]. OS are produced by salivary glands [35]. In the present study, we correspondingly detected the specific overexpression of all RfARSBs in salivary glands, the mRNA abundance of which was much higher than that in other tissues/organs, including the head, epidermis, fat body, gut, and hemolymph.…”
Section: Discussionmentioning
confidence: 64%
“…In recent years, this phenomenon has also been found to be increasingly common in other insects [33,34]. Previously, a sialotranscriptome of adult female, Culex tarsalis, revealed that oral secretions (OS) were generally produced by salivary glands [35].…”
Section: Introductionmentioning
confidence: 96%
“…Additional SNPs in the reference sequence compared to multiple sequenced KNWR individuals were removed by extracting the consensus sequence from a single male KNWR library mapped to the reference using bcftools. Annotations were performed using Maker (v.2.31.10) with the Culex tarsalis transcriptome (Ribeiro et al 2018) and Cx. quinquefasciatus protein sequences (CpipJ2.4).…”
Section: Pacbio Genome Assemblymentioning
confidence: 99%